A comparative study of spark plasma sintering and hybrid spark plasma sintering of 93W–4.9Ni–2.1Fe heavy alloy. (February 2016) - Shongwe, Mxolisi Brendon; Diouf, Saliou; Durowoju, Mondiu Olayinka; Olubambi, Peter Apata; Ramakokovhu, Munyadziwa Mercy; Obadele, Babatunde Abiodun
Abstract: Mixed 93W–4.9Ni–2.1Fe powders were sintered via the spark plasma sintering (SPS) and hybrid spark plasma sintering (HSPS) techniques with 30 mm and 60 mm samples in both conditions. After SPS and HSPS, the 30 mm and 60 mm alloys (except 60 mm-SPS) had a relative density (> 99.2%) close to the theoretical density. Phase, microstructure and mechanical properties evolution of W–Ni–Fe alloy during SPS and HSPS were studied. The microstructural evolution of the 60 mm alloys varied from the edge of the sample to the core of the sample. Results show that the grain size and the hardness vary considerable from the edge to the core of sintered sample of 60 mm sintered using conventional SPS compared to hybrid SPS. Similarly, the hardness also increased from the edge to the core. Furthermore, the 60 mm-HSPS alloy exhibited improved bending strength of 1115 MPa when compared to that of 60 mm-SPS, 920 MPa. The intergranular fracture along the W/W grain boundary is the main fracture modes of W–Ni–Fe, however in the 60 mm-SPS alloy peeling of the grains was also observed which diminished the properties. The mechanical properties of SPS and HSPS 93W–4.9Ni–2.1Fe heavy alloys are dependent on the microstructural parameters such as tungsten grain size and overall homogeneity. Highlights: The 30 mm and 60 mm alloys (except 60 mm-SPS) had a relative density of > 99.2%. The grain size and hardness vary considerable from the edge to the core of 60 mm-SPS. The 60 mm-HSPS alloy exhibits improved bending strength than the 60 mm-SPS. Intergranular fracture along W/W grain boundary is the main fracture. Mechanical properties are dependent on tungsten grain size and overall homogeneity.